New Museums - Donzel, Catherine; Donnat, Véronique; Gardner, Lisa (Paris : Telleri, 1998)
Ibos & Vitart ; Stirling, James and Wilford, Michael ; Bruno, Andrea ; Amadó and Domènech ; Judd, Donald ; Foster, Norman ; Koolhaas, Rem ; Vieira, Alvaro Siza ; PEI, I. M. ; Ito, Toyo ; Rossi, Aldo ; Moneo Valles, José Rafael ; Holl, Steven ; Herzog & de Meuron ; Piano, Renzo ; Meier, Richard ; Gehry, Frank O.
boek